IDENTIFICATION OF GENETIC DIVERSITY CYTOCHROME OXIDASE SUBUNIT II (COII) MITOCHONDRIAL GENE AS GENETIC MARKER FOR ANISAKIS SPECIES IN Euthynnus affinis - Utami, Prasetyarti; Handayani, Niken Satuti Nur; Kunda, Rony Marsyal (Jurnal Kedokteran Hewan, 2017)
ABSTRACTThis study aimed to get specific genetic marker for Anisakis sp. identification on mackerel tuna using gene sequence cytochrome oxidase subunit II (COII) mitochondrial deoxyribonucleic acid (mtDNA) and to identify taxonomic affiliation between Anisakis sp. from Indonesia and others Anisakis sp. from GenBank database. This study started with sample collections at three fish auctions in Cilacap (Central Java), morphology classification, DNA isolation, and molecular based identification using polymerase chain reaction (PCR) and sequencing methods. Molecular based identification of Anisakis used gene amplification COII mtDNA as a cell target prior to sequence. Morphology characteristic results showed that Anisakis nematodes which infected mackerel tuna classified as type II L3 larvae. Molecular based identification showed significant result, which found 530 bp COII DNA gene fragment similar to target cell. Gene sequencing alignment results of COII Anisakis gene compared with GenBank showed 11 different nucleotide sites that can be used as genetic barcode for Indonesian Anisakis sp. This study showed that Anisakis sp. infected mackerel tuna in Java Sea is Anisakis physeteris and considered as zoonosis.